2020
DOI: 10.3390/ani10091515
|View full text |Cite
|
Sign up to set email alerts
|

Claw Trimming as a Lameness Management Practice and the Association with Welfare and Production in Dairy Cows

Abstract: Lameness resulting from claw lesions remains a pressing welfare issue in dairy cows. Claw trimming (CT) is a common practice for prevention and management of clinically lame cows. This review summarizes the results of studies that have investigated various claw trimming (CT) methods, their application in lameness management, and associations with the welfare and production of dairy cows. The papers included in this review fulfilled the following inclusion criteria: published in peer review journal or book chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Therefore, prevention or reduction in lameness in cows with scores ≥ 3 during the dry period and early lactation is anticipated to have beneficial effects on these and other parameters and welfare [ 14 , 17 , 23 ]. This can be achieved by checking all cows for lameness at dry-off and routine claw trimming, and treatment at dry-off and again at 40 to 60 DIM together with concurrent regular locomotion scoring at two-week intervals [ 14 , 16 , 46 , 69 ]. Conversely, an explanation for these rather high incidence risks of lameness in dry cows and cows in the first 100 DIM is that many farmers do not routinely check cows for lameness at dry-off and during the first 100 DIM, and do not perform hoof trimming at these critical time points [ 62 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, prevention or reduction in lameness in cows with scores ≥ 3 during the dry period and early lactation is anticipated to have beneficial effects on these and other parameters and welfare [ 14 , 17 , 23 ]. This can be achieved by checking all cows for lameness at dry-off and routine claw trimming, and treatment at dry-off and again at 40 to 60 DIM together with concurrent regular locomotion scoring at two-week intervals [ 14 , 16 , 46 , 69 ]. Conversely, an explanation for these rather high incidence risks of lameness in dry cows and cows in the first 100 DIM is that many farmers do not routinely check cows for lameness at dry-off and during the first 100 DIM, and do not perform hoof trimming at these critical time points [ 62 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, painful claw lesions do not necessarily lead to premature culling. Outcomes always depend on how early and how effectively treatments are carried out, which can vary greatly from farm to farm [ 16 , 42 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, functional hoof trimming was performed at intervals of approximately four and three months, which is an unusually short interval compared to common practice in many dairy herds [ 60 , 61 , 62 ]. This management measure could also be cited as an explanation for the low prevalence of lameness and claw lesions in the 24 first-lactation cows.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its perceived widespread practice, evidence supporting trimming technique and optimal frequency of trimming are limited for the modern dairy cow. 2 A recent study surveyed 61 dairy farms to determine risk factors associated with lameness. 3 It was reported that 63.6% of farms undertook preventive hoof trimming, with 23% of respondents implementing a preventive trim between 60 and 100 days of lactation, which was significantly associated with a decreased lameness prevalence.…”
Section: Introductionmentioning
confidence: 99%